Meretas Polarisasi Doktrin Kehidupan Jemaat Mula-Mula dan Implementasinya bagi Pendidikan Agama Kristen Keluarga Masa Kini - Remegises danial Yohanis Pandie; Sozawato Telaumbanua; Samuel Siringo ringo; Mariyanti Adu; Yeheskiel Obehetan (Departemen Literatur dan Media, Sekolah Tinggi Teologi Arrabona Bogor, 2023)
The objective of this article is to delve into the underlying meanings within the lives of the early congregation and to link them with their relevance in the lives of contemporary Christian families. Within this article, an analysis is conducted on the concepts of life during the era of the apostles, with the intention of elucidating how the early congregation maintained resilience amidst challenging circumstances and provided a profound perspective for modern Christian families. The analysis of the lives of the early congregation is anticipated to provide valuable insights for Christian families. The inquiries addressed within this study are how the concepts of the early congregation's life can be actualized through Christian religious education within the milieu of modern Christian families, along with the model of Christian religious education that can be embraced by these families. To address these inquiries, a qualitative research methodology is employed, encompassing the analysis of pertinent literature including books, articles, and journals. The research findings ascertain that the principles of the early congregation's life remain pertinent and can be applied in the contemporary context through elements of hope, steadfast faith, and love. As such, Christian families are urged to comprehend and implement God's messages in confronting the challenges of daily life. Tujuapenulisan artikel ini adalah bertujuan untuk menggali makna yang terkandung dalam kehidupan jemaat mula-mula yang masih relevan dengan kehidupan jemaat masa kini. Pembahasan artikel ini mengetengahkan ulasan konsep-konsep Paulus dalam mengajari jemaat mula-mula untuk tetap kuat dalam tekanan dan diyakini memberi pemaknaan lebih kepada keluarga Kristen masa kini. Evaluasi dari kehidupan jemaat mula-mula diharapkan memberikan masukan bagi keluarga Kristen masa kini agar menjadi lebih baik. pertanyaan yang berusaha dijawab dalam penelitian ini adalah bagaimana implementasi konsep kehidupan jemaat mula-mula melalui pendidikan agama Kristen keluarga dalam kehidupan keluarga masa kini? Model pendidikan agama Kristen seperti apa yang bisa digunakan untuk diterapkan dalam keluarga?. Adapun metode yang digunakan dalam penelitian ini adalah studi pustaka. Dalam Kajian ini, peneliti menemukan bahwa Konsep hidup jemaat mula-mula masih relevan dan dapat diimplemetasikan dalam konteks masa kini melalui hidup dalam pengharapan, kokoh dalam iman dan hidup dalam kasih. Keluarga Kristen perlu menyadari dan memahami maksud Tuhan dalam setiap tantangan hidup yang datang silih berganti.